A Probe into Thai EFLTeachers’ Outlook on the Utilization of AI as Pedagogical Tool in EFL Classroom in Thailand - Cantika, Cantika; Hasnah, Yeni (Journal of English Language and Education, 2025)
This study explores English as a Foreign Language (EFL) teachers’ perspective on the integration of Artificial Intelligence (AI) in English language classrooms in Thailand. With the rise of AI-powered tools such as QuillBot, education is undergoing a transformation that promises personalized learning, improved student engagement, and enhanced language skills. Through qualitative methods, including open-ended questionnaires administered to two EFL teachers at Sri Aman Suska School No. 54, the research reveals generally positive perceptions of AI's potential in supporting instruction. Teachers reported that AI facilitated writing tasks, boosted student confidence, and supported personalized learning. However, challenges such as limited digital access, student overreliance, and lack of formal training were also identified. Despite these concerns, both educators emphasized the importance of balancing technology with human interaction, promoting ethical use, and encouraging critical thinking. The findings suggest that while AI holds significant promise for EFL education, its implementation must be carefully managed through teacher support, infrastructure development, and pedagogically sound integration strategies.